Các phụ thuộc yếu trong mô hình dữ liệu quan hệ - Thi, Vu Duc; Anh, Nguyen Kim (Journal of Computer Science and Cybernetics, 2018)
One of  the main concepts in relational database theory is the full family of functional dependencies, that was first axiomatized by W.W.Armstrong [1]. The full family of weak dependencies have also been introduced and axiomatized [4, 5]. In this paper, we give some new results about weak dependencies. We give a necessary and sufficient condition for W+R = W+, and then we construct an effective combinatorial algorithms to  determine irredundant relation R’ for an arbitrary given relation R such that R’ Í R, W+R’ = W+R.